Postoperative complications after head and neck operations that require free tissue transfer - prevalent, morbid, and costly. Issue 8 (October 2017) - McMahon, J.; Handley, T.P.B.; Bobinskas, A.; Elsapagh, M.; Anwar, H.S.; Ricciardo, P.V.; McLaren, A.; Davis, R.; Syyed, N.; MacIver, C.; Wales, C.; Hislop, W.S.; et al.
Abstract: To understand and reduce the impact of postoperative complications, we studied 568 patients who had had operations over 72 months in our hospital. Multivariate analysis indicated that factors indicative of coexisting conditions (including activated systemic inflammation) and the complexity of the operation are primary determinants of postoperative complications. The enhanced recovery after surgery (ERAS) care pathway did not have an effect on their occurrence or severity. Systematic study of patients' toleration of major head and neck operations is required, as optimal perioperative care pathways remain elusive.